Influencia en educación sobre salud dental y su relación con enfermedades bucodentales en niños. Revisión Bibliográfica - Castro Lara, Christopher Patricio (2021)
The lack of education about dental health intervenes in different ways in children, causing an increase in the prevalence or development of oral diseases. The prevalence of oral pathologies in children is high and largely extend related to poor oral hygiene. Identify the influence of dental health education and its relationship with oral diseases in children, determine which oral pathologies are prevalent in schoolchildren due to poor oral hygiene and identify the lack of education in nutrition and its relationship with dental caries are the objects of study of this investigative work. It is a bibliographic review paper where a systematic review of bibliographic data, journals, theses, books, search for scientific articles in Spanish, English and Portuguese was carried out on different platforms such as: PubMed, Scielo, Cochrane Library, Google Scholar, ResearchGate, ScienceDirect, Dialnet and MedLine. The universe was based on 53 articles with a scientific basis, the articles that contained the necessary information to obtain the results of the objectives set, articles in Spanish, English and Portuguese, studies that did not exceed 10 years of publication were selected, taking into account all these aspects, a sample of 20 studies were obtained. These articles determine that oral health education programs have a positive impact on children, reducing the prevalence or preventing the development of oral diseases. Poor oral hygiene will cause or increase the risk or probability that children will develop or present oral pathologies; when there is poor oral hygiene, the pathology that is most prevalent in children is dental caries, followed by gingivitis. A correct and balanced diet will decrease the likelihood that children will have or develop dental decay. The lack of education about nutrition in children and their parents or guardians is a predisposing factor to the appearance of cavities. The different interventions carried out on the groups involved have a positive influence, improving knowledge about oral health, children's eating habits, and their tooth brushing. Key Words: Oral hygiene, dental health, oral pathology, Feeding Behavior.